Thromboembolic and hemorrhagic risks after vaccination against SARS-CoV-2: a systematic review and meta-analysis of randomized controlled trials - Noppacharn Uaprasert (BMC, 2021)
Abstract Background Thromboembolic and bleeding events after vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are major public concerns leading to vaccine hesitancy. Due to low incidence, an individual randomized controlled trial (RCT) is underpowered to determine whether SARS-CoV-2 vaccines increase the risks of thromboembolism and hemorrhage. Methods We performed a literature search using PubMed, EMBASE, Cochrane, medRxiv databases, and reference lists of relevant articles to identify RCTs that reported thromboembolic, hemorrhagic events, and thromboembolism/hemorrhage-related death after SARS-CoV-2 vaccination. The primary aim of this systematic review and meta-analysis was to estimate the pooled thromboembolic risk related to SARS-CoV-2 vaccines compared to placebo. The secondary outcomes included estimating the risks of arterial thromboembolism (ATE), venous thromboembolisms (VTE), hemorrhage, thrombocytopenia, and thromboembolism/hemorrhage-related death. Results Eight RCTs of 4 vaccine platforms comprised of 195,196 participants were retrieved. SARS-CoV-2 vaccines were not associated with an increased risk of overall thromboembolism (risk ratio [RR], 1.14; 95% CI [confidence interval], 0.61–2.14; I2 = 35%), ATE (RR, 0.97; 95% CI, 0.46–2.06; I2 = 21%), VTE (RR, 1.47; 95% CI, 0.72–2.99; I2 = 0%), hemorrhage (RR, 0.97; 95% CI, 0.35–2.68; I2 = 0), and thromboembolism/hemorrhage-related death (RR, 0.53; 95% CI, 0.16–1.79; I2 = 0). Compared to the baseline estimated risk of these outcomes in participants administered placebos, the risk differences with vaccines were very small and not statistically significant. These findings were consistent in the subgroup analysis across 4 vaccine platforms. Conclusion Vaccines against SARS-CoV-2 are not associated with an increased risk of thromboembolism, hemorrhage, and thromboembolism/hemorrhage-related death.